Thermoelectric Characterization of Electronic Properties of GaMnAs Nanowires - Phillip M. Wu; Waldomiro Paschoal; Sandeep Kumar; Christian Borschel; Carsten Ronning; Carlo M. Canali; Lars Samuelson; Håkan Pettersson; Heiner Linke (Journal of Nanotechnology)
Nanowires with magnetic doping centers are an exciting candidate for the study of spin physics and proof-of-principle spintronics devices. The required heavy doping can be expected to have a significant impact on the nanowires' electron transport properties. Here, we use thermopower and conductance measurements for transport characterization of Ga0.95Mn0.05As nanowires over a broad temperature range. We determine the carrier type (holes) and concentration and find a sharp increase of the thermopower below temperatures of 120 K that can be qualitatively described by a hopping conduction model. However, the unusually large thermopower suggests that additional mechanisms must be considered as well.